2017
DOI: 10.5114/aoms.2017.65233
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein A1 polymorphisms and risk of coronary artery disease: a meta-analysis

Abstract: A b s t r a c tIntroduction: It has been reported that APOA1 -75G/A polymorphism might be associated with susceptibility to coronary artery disease (CAD). Owing to mixed and inconclusive results, we conducted a meta-analysis to systematically summarize and clarify the association between APOA1-75G/A polymorphism and the risk of CAD. Material and methods: A systematic search of studies on the association of single nucleotide polymorphisms (SNP) with susceptibility to CAD was conducted. A total of 9 case-control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 32 publications
(32 reference statements)
1
16
0
Order By: Relevance
“…First, cases with severe heart failure showed a decrease in ficolin-3 levels, and these low levels of ficolin-3 are a consequence of consumption after binding to altered self-structures in the myocardial cell wall, with subsequent complement activation, leading to inflammation and tissue damage. Xu et al [42] reported that the minor allele of the apolipoprotein A1 -75G/A polymorphism is a protective factor for coronary artery disease, especially in the studies consistent with HWE.…”
Section: Discussionmentioning
confidence: 99%
“…First, cases with severe heart failure showed a decrease in ficolin-3 levels, and these low levels of ficolin-3 are a consequence of consumption after binding to altered self-structures in the myocardial cell wall, with subsequent complement activation, leading to inflammation and tissue damage. Xu et al [42] reported that the minor allele of the apolipoprotein A1 -75G/A polymorphism is a protective factor for coronary artery disease, especially in the studies consistent with HWE.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of subjects with an FH of premature CAD showed a higher frequency of lipid disorders, elevated lipoprotein a and homocysteine levels in this group of patients [21–25].…”
Section: Discussionmentioning
confidence: 99%
“…These events subsequently lead to the development of atherosclerosis, heart disease, and myocardial infarction [9,10]. However, there are various mechanisms that increase the risk of CHD, such as high blood pressure, thrombosis, arrhythmia, inflammation, endothelial dysfunction, insulin resistance, oxidative stress, cigarette smoking, family history, obesity, and overall dietary patterns, among others [10,25]. Lipid levels are another such mechanism that have been suggested to be "strong" risk factors for CVD and mortality, such as high cholesterol, triglycerides (TGs), low-density lipoprotein cholesterol (LDL-C), lipoprotein(a) (Lp(a)), very-low-density lipoprotein cholesterol (VLDL-C), and low high-density lipoprotein cholesterol (HDL-C) [10,26].…”
Section: Introductionmentioning
confidence: 99%